Rancang Bangun Sistem Pendeteksi Kebocoran Gas Berbasis Internet Of Thing (IoT) - Syarif Ishak Allkadri; Yudi Chandra (entries, 2023)
Gas is something that is very much needed in human life both in households and industries. However, there are many cases of fire caused by leaks from the cylinder or gas storage area. The cause of leaking gas cylinders can occur due to leaks in hoses, tubes or regulators that are not installed properly and the gas cylinders that are distributed are of poor quality or damaged. The design of this gas leak detection system uses the MQ-2 Sensor, Buzzer, Led Red, Green, and NodeMCU ESP8266. A gas leak detection system based on Internetx of Things (IoT) technology was built as a solution to reduce the risk of fire, explosion and gas poisoning which often occur due to gas leaks that are not detected quickly. With this system, users can obtain higher security and comfort in their activities, and users can quickly take preventive and extinguishing measures in the event of a gas leak. Notification of a gas leak and the level of the leak will be displayed on the user's smartphone via the WhatsApp application, so that when the user is not near the location of the gas leak, the user can still find out about it. The test results show that the program iscapable of running tools to detect gas levels and isable to provide warnings via red LEDs, buzzers, exhaust fans, and notifications from WhatsApp. Keywords: MQ-2 Sensor, NodeMCU ESP8266, Buzzer, Exhaust Fan, WhatsApp